Looking into the dragons of cultural ecosystem services. Issue 1 (1st January 2020) - Gould, Rachelle K.; Adams, Alison; Vivanco, Luis
Abstract: Cultural ecosystem services research is in a somewhat tumultuous state. The cultural ecosystem services (CES) idea is seen simultaneously as a welcoming, expansive addition to conservation policy-making and as a strange, square-peg-in-a-round-hole concept that should be replaced by a more appropriate metaphor or conceptual structure. This confluence of interest and skepticism suggests an opportune moment to take stock of CES, both as a concept and growing scholarly field. Here, we focus on dilemmas that characterize and constitute CES as a field of empirical inquiry and practice. We describe five tensions that characterize the field (and mirror tensions in interdisciplinary work more broadly): universalism and anti-universalism; reductionism and non-reductionism; historical and ahistorical approaches; politicized and depoliticized approaches; and objectivity and situated knowledges. We then suggest five non-mutually-exclusive roles that CES research can (and does) play: The Convener/Illuminator; the Process Police Officer; the Translator; the Revolutionary; and the Policy In-fighter. We provide examples of each tension and role, and posit that clarity and reflexivity may help to make sense of a fertile, if sometimes confusing, interdisciplinary field. Making more sense of, and being more explicit about, the contradictions and contributions of the CES field, can, we suggest, aid decision-makers, CES researchers, and others to better include these values in environmental management.